Enteric Methane Emission from Cattle Grazing Systems with Cover Crops and Legume–Grass Pasture - Gere, José Ignacio (2024)
This study aims to quantify enteric methane (CH4) emission and dry matter intake (DMI) in beef steers under two rotational grazing systems: (i) a mixture of cover crops (vetch + ryegrass + forage radish) (CC) and (ii) alfalfa and fescue pasture (AFP). Eighteen Hereford steers were divided into two groups (nine steers per group), assigned to either the CC or AFP. Methane emissions were measured using the SF6 tracer technique. The results showed that steers grazing CC produced 29% less CH4 in g/d compared to those on the AFP (119.1 vs. 167.1 g/d for CC and AFP, p < 0.05) and 36% less CH4 yield (4.3 vs. 6.7% of gross energy intake). However, average daily gain (ADG), DMI, and CH4 intensity (gCH4/kg ADG) did not significantly differ between treatments. The integration of CC in a cattle grazing system has the potential to reduce CH4 emissions by improving forage quality.